Working with parents of aggressive children : a practitioner's guide - Cavell, Timothy A.; Quetsch, Lauren B. (Applying psychology in the schools, 2023)
"This second edition of Working With Parents of Aggressive Children features new scholarship in children's emotional socialization and childhood aggression and offers parenting interventions developed through the lens of equity, diversity, and inclusion. Healthy parent-child relationships reflect parents' capacity to accept, contain, and lead their children, and under-girding healthy-parent child relationships are parents' goals, parents' health, and family structure. This comprehensive guide shows mental health providers how to discuss setting reasonable expectations and goals that are attainable through therapy, promoting parent self-care, and promoting family structure. Instead of a one-size-fits-all approach, the authors explain how clinicians can tailor their work to the unique needs of each family. They offer compelling, realistic examples that accurately reflect the range of diversity that exists among parents and families, and examine the opportunities and challenges that can arise when working with families from diverse backgrounds. "--